High-Voltage Electrical Pulses in Oncology: Irreversible Electroporation, Electrochemotherapy, Gene Electrotransfer, Electrofusion, and Electroimmunotherapy - Geboers, Bart; Scheffer, Hester J; Graybill, Philip M; Ruarus, Alette H; Nieuwenhuizen, Sanne; Puijk, Robbert S; van den Tol, Petrousjka M; Davalos, Rafael V; Rubinsky, Boris; de Gruijl, Tanja D; Miklavčič, Damijan; Meijerink, Martijn R (Radiology, 2020)
This review summarizes the use of high-voltage electrical pulses (HVEPs) in clinical oncology to treat solid tumors with irreversible electroporation (IRE) and electrochemotherapy (ECT). HVEPs increase the membrane permeability of cells, a phenomenon known as electroporation. Unlike alternative ablative therapies, electroporation does not affect the structural integrity of surrounding tissue, thereby enabling tumors in the vicinity of vital structures to be treated. IRE uses HVEPs to cause cell death by inducing membrane disruption, and it is primarily used as a radical ablative therapy in the treatment of soft-tissue tumors in the liver, kidney, prostate, and pancreas. ECT uses HVEPs to transiently increase membrane permeability, enhancing cellular cytotoxic drug uptake in tumors. IRE and ECT show immunogenic effects that could be augmented when combined with immunomodulatory drugs, a combination therapy the authors term . Additional electroporation-based technologies that may reach clinical importance, such as gene electrotransfer, electrofusion, and electroimmunotherapy, are concisely reviewed. HVEPs represent a substantial advancement in cancer research, and continued improvement and implementation of these presented technologies will require close collaboration between engineers, interventional radiologists, medical oncologists, and immuno-oncologists.